A Collaborative Maternal Arrest Safety Initiative. Issue 1 (June 2015) - Liner, Mary Ann; Wheeler, Mary; Shafer, Mildred Elaine; Croland, Joshua
<x xml:space="preserve">Abstract</x> Poster Presentation Purpose for the Program The American Heart Association's (AHA) 2010 guidelines address cardiac arrest in pregnancy by providing a published algorithm and pregnancy specific modifications for management. A health care provider's ability to react prudently in an unexpected situation is one of the most critical factors in creating a positive outcome in an obstetric emergency. Researchers have shown that advanced cardiac life support (ACLS) certification may not necessarily translate to adequate performance of maternal resuscitation skills during an actual arrest. This maternal arrest pilot program prepares participants how to manage this rare unpredictable obstetric emergency through simulated training experiences that pose no risk to the mother or fetus. Proposed Change OSF Saint Francis Medical Center is a perinatal referral center with a neonatal intensive care unit (NICU) and Level‐I trauma center located in central Illinois. The management of a maternal cardiac arrest requires the collaboration of several teams (obstetric, neonatal, anesthesia, nursing, hospital code, emergency medicine, and prehospital emergency medical services [EMS]) who rarely collaborate to come together to deliver consistent, excellent patient care. The ACLS classes at OSF do not include a comprehensive review of maternal resuscitation. This obstetric‐focused pilot program will bridge this knowledge gap to include a didactic module and simulation component specific to resuscitation of the pregnant woman in conjunction with the current ACLS training program. This program for maternal arrest can span the entire OSF HealthCare system north central region to improve performance during a maternal arrest. Implementation, Outcomes, and Evaluation An interdisciplinary team was involved in the pilot development and will serve as trainers. A survey to assess current ACLS knowledge on maternal arrest will be administered before participants complete the didactic maternal arrest eLearning module. Data will be collected for comparison prelearning and postlearning. The participants include obstetric and emergency residents, registered nurses, anesthesia providers, and neonatal nurse practitioners. Using an obstetric mannequin, the in situ simulation component will be used to analyze the primary and secondary responder's performance using real‐life maternal arrest scenarios, detect areas of deficiency in using the AHA‐recommended algorithm, and discuss performance improvements. Presimulation and postsimulation confidence surveys will be completed. Implications for Nursing Practice Training, communicating, and solving problems in teams can affect maternal and fetal survival during a cardiac arrest. This collaboration will increase job satisfaction for all responders.